2017
DOI: 10.1245/s10434-017-5915-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bilateral Prophylactic Mastectomy and Immediate Reconstruction on Health-Related Quality of Life in Women at High Risk for Breast Carcinoma: Results of the Mastectomy Reconstruction Outcomes Consortium Study

Abstract: Background Although bilateral prophylactic mastectomy (BPM) can reduce the risk of breast cancer, the decision to proceed surgically can have significant consequences and requires careful deliberation. To facilitate decision-making for women at high risk for breast carcinoma, the risks and benefits of BPM should be well-elucidated. We sought to determine the effects of BPM and immediate reconstruction on health-related quality of life outcomes among a multisite cohort of women at high risk for breast carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
3
36
1
1
Order By: Relevance
“…Pleasure score † 12 (9-16) 11 (9)(10)(11)(12)(13)(14) .56 11 (9)(10)(11)(12)(13)(14) 12 (9)(10)(11)(12)(13)(14)(15) .34…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Pleasure score † 12 (9-16) 11 (9)(10)(11)(12)(13)(14) .56 11 (9)(10)(11)(12)(13)(14) 12 (9)(10)(11)(12)(13)(14)(15) .34…”
Section: Discussionunclassified
“…In order to appropriately counsel women regarding the relative benefit of cancer risk reduction and the health consequences of RRSO, it is important to understand the impact of pre-versus postmenopausal RRSO relative to other factors such as age, cancer and cancer treatment on sexual and menopausal symptoms 6,7 and to be able to provide realistic expectations regarding immediate post-operative versus long-term impact. [8][9][10] The question of what happens after this immediate surgically induced menopause is not clearly described but is important for patient counseling. [8][9][10] The question of what happens after this immediate surgically induced menopause is not clearly described but is important for patient counseling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in anxiety and cancer‐related distress among BRCA1 /2 carriers was notable when compared to both carriers who opted for surveillance and non‐carrier individuals. McCarthy et al . and Pusic and co‐workers published results from the Mastectomy Reconstruction Outcomes Consortium and reported that women who underwent RRM with immediate reconstruction had significantly decreased anxiety 1 and 2 years after surgery compared with baseline scores.…”
Section: Hereditary Breast and Ovarian Cancermentioning
confidence: 98%
“…Furthermore, RRM appears to decrease cancer‐related anxiety. A prospective study evaluated women with high‐risk cancer who underwent RRS (RRM, RRM plus RRSO, or RRSO alone) in comparison with age‐ and risk‐matched control patients in the same high‐risk group who did not have surgery.…”
Section: Hereditary Breast and Ovarian Cancermentioning
confidence: 99%